Internet of (Healthcare) Things Based Monitoring for COVID-19+ Quarantine/ Isolation Subjects Using Biomedical Sensors, A Lesson from the Recent Pandemic, and an Approach to the Future. - Azarudeen Mohamed Arif; Abubaker M. Hamad; Montasir Mohamed Mansour (Department of Electromedical Engineering, POLTEKKES KEMENKES SURABAYA and IKATEMI, 2023)
The COVID-19+ pandemic has brought into keen focus the necessity to utilize and enforce our digital infrastructure for remote patient monitoring based on IoT (Internet of Things) technology since quarantines and isolations are playing a vital role in containing its spread. As of date, many viral tests and vaccines are in use while few drugs are in experimental stages, but there is always need for possibilities for increasing reliability of disease detection and monitoring at both levels of individual and society, and such aim can be supported by wearable biomedical sensors devices. Previously, wearable devices have been used to monitor physiological parameters during daily human living activities. Still, the investment of such technologies toward predicting infection by COVID-19+ remains essential to alert potential patients and start sequence of health systems intervention. It was found that wearable devices increased patients’ compliance to healthcare advice. Thus, in this perspective review, we have proposed an IoT based system to monitor the quarantine / isolation subjects during COVID-19+ and similar pandemic and quarantine observation. This wearable prototype, associated with the bundled mobile app, act to reports and tracks/monitoring the quarantined individuals. IoT based quarantine/isolation monitoring system is contact-free that could benefit especially healthcare professionals to lower the risk of exposure to infective pathogens. Current manuscript describes clinically relevant physiological human parameters that can be measured by wearable biomedical sensors and monitored based on IoT technology and their role in health tracking, stability, and recovery of COVID-19++ve individuals and front-line health workers. This paper aimed at initiation of an approach among front-line healthcare workers as well as biomedical engineers for developing digital healthcare platforms of monitoring and managing such pandemic.